Valoração ambiental da erosão marginal do perímetro irrigado Cotinguiba / Pindoba no baixo São Francisco sergipano - Oliveira, Aline Suze Torres de (2006)
The accelerated edges erosion in bass course of the river San Francisco s became of the actions sponsored for the man and development politics gone back to construction and barrages operations and energy generation. This work had as objective the Oportunity Cost Method for monetary valuation of ambient recovery, through cost-benefit and to quantify the economic losses of bass San Francisco s edges right, caused by marginal erosion in the space of the irrigated perimeter Cotinguiba/Pindoba . The loss of hectares in the period from 1975 to 2005 approximately 76 hectares , what it results an annual medium damage of 2,5 hectares . The oportunity cost in the environmental recovery of the researched area was R$ 396.796,00 and the rude value is R$ 101.040,52. If we verify for a cost-benefit analysis in the stated period of ten years, applied in a tax discount of 15% translated for the present value, we would have a liquid benefit of R$ 61.598,65. The agents causers of marginal erosion are recognized by the retreat of ciliary forest for the implantation of the perimeter Cotinguiba /Pindoba by the construction of diverse barrages to the long one of river course. The gotten data will serve of alert and for subsidy for the decisions linked to planning and environmental administration of the area with intention of minimizing externalidades .